The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2cp02364d
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the inverted singlet–triplet gap of the 5th generation light-emitting molecules

Abstract: Excitation energies of the lowest singlet and triplet state of molecules whose first excited singlet state lies energetically below the first triplet state have been studied computationally at (time-dependent) density...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 78 publications
1
56
0
Order By: Relevance
“…65–71 Previously, we showed that ΔSCF calculations at the DFT level of theory predict singlet–triplet inversion of heptazine and five other related INVEST molecules. 22 However, the SCF wavefunctions of the S 1 state suffer from severe spin contamination ( ŝ 2 > 1), and Δ E ST depends heavily on the employed functional. Similar problems arose for the molecules studied here.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…65–71 Previously, we showed that ΔSCF calculations at the DFT level of theory predict singlet–triplet inversion of heptazine and five other related INVEST molecules. 22 However, the SCF wavefunctions of the S 1 state suffer from severe spin contamination ( ŝ 2 > 1), and Δ E ST depends heavily on the employed functional. Similar problems arose for the molecules studied here.…”
Section: Resultsmentioning
confidence: 99%
“…However, we recently proposed that the ca 1%-higher percentage of doubles in S 1 is the reason for its energy stabilization with respect to the T 1 state. 22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 With the prospect of superior emissive properties, it is imperative to find new classes of molecules with singlet-tripet inversions. Given the historic lack of focus on the possible existence of Hund's rule violations among excited states, and because inverted singlet-triplet gaps can only be modelled using high-level quantum chemical methods, 14,[23][24][25][26][27][28] we suggest that there may be many cases of excited state singlet-triplet inversions among already synthesized molecules.…”
mentioning
confidence: 99%